(untitled) (Vietnam Journal of Community Medicine, 2026)
Infertility is a reproductive health problem that affects the lives of many wives. The current world infertility rate is about 15%. Current assisted reproductive technologies can solve the problem in most cases. However, there are still a significant number of couples who are unable to conceive even after assisted reproduction is available. In such cases, stem cell therapy can offer hope to couples who wish to have children who are media similar to them. Extensive research is underway on induced pluripotent stem cells (iPSCs). Similarly, mesenchymal stem cells (MSCs) such as skeleton, adipose tissue, menstrual blood, endometriosis, slurry, and placenta, are gaining popularity for application in reproductive medicine. However, more large-scale clinical trials are needed for evidence of the safety and efficacy of stem cell-based therapies in the field of human reproduction.